If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4(1 + -3x) = 4x + -1(x + 1) 5x + (1 * -4 + -3x * -4) = 4x + -1(x + 1) 5x + (-4 + 12x) = 4x + -1(x + 1) Reorder the terms: -4 + 5x + 12x = 4x + -1(x + 1) Combine like terms: 5x + 12x = 17x -4 + 17x = 4x + -1(x + 1) Reorder the terms: -4 + 17x = 4x + -1(1 + x) -4 + 17x = 4x + (1 * -1 + x * -1) -4 + 17x = 4x + (-1 + -1x) Reorder the terms: -4 + 17x = -1 + 4x + -1x Combine like terms: 4x + -1x = 3x -4 + 17x = -1 + 3x Solving -4 + 17x = -1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -4 + 17x + -3x = -1 + 3x + -3x Combine like terms: 17x + -3x = 14x -4 + 14x = -1 + 3x + -3x Combine like terms: 3x + -3x = 0 -4 + 14x = -1 + 0 -4 + 14x = -1 Add '4' to each side of the equation. -4 + 4 + 14x = -1 + 4 Combine like terms: -4 + 4 = 0 0 + 14x = -1 + 4 14x = -1 + 4 Combine like terms: -1 + 4 = 3 14x = 3 Divide each side by '14'. x = 0.2142857143 Simplifying x = 0.2142857143
| 7+X= | | ax^2+c=0 | | r^3-3r^2-9r-5=0 | | 7.4+1.5y=-2.267+.167y | | (3p*2n)-(2p*3n-2p)-(2np+2p)= | | 30x-5y=-68 | | 10x+15y=74 | | 8(x+8)=82-(x-9) | | .3(p-2)=5-0.6p | | 2(y+6)=y-1 | | 9a-8(a-5)=6 | | x^3+x^2-12x= | | A+20=10 | | A+20=2.5 | | 4x-13y=67 | | 3x+3=3x+1 | | 12x+18y=30 | | 5x+20-7x=7(3+x)-3x | | y=25x+60 | | 8x+4y=8 | | (x-3)(x-1)= | | X+2X+X+20=180 | | 1-xy-20X^2b^2= | | 9(t+4)=0 | | 1-xy-2X^2b^2= | | -9x(x-1)= | | 122.00=5x+4y | | X+X+30+60=180 | | 5(24.4-.8y)+4y=122.00 | | (5s-4)(6s+6)= | | 105-84=27y-34y | | 105-84=27y-34 |